A method of preparing a sheltering aerogel composite
Patent Information
- Application Number
- CN202511550521.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-28
- Publication Date
- 2026-10-13
AI Technical Summary
但是气凝胶材料对热辐射的阻隔性能差,因此阻碍了气凝胶复合纤维材料在高超声速发动机、飞行器舱段、高端装备等对隔热性能要求较高的领域的应用;
[0020]采用上述进一步技术方案的有益效果在于:通过加入改性剂能够把纤维增强气凝胶复合材料内部的羟基置换出来,有利于防潮,隔热效果好。
Smart Images

Figure CN122897657A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of aerogel material preparation technology, and specifically relates to a method for preparing a shielding aerogel composite material. Background Technology
[0002] Aerogel composite fiber materials, as thermal insulation materials, have high barrier properties against heat convection and heat conduction, while also having low material density, light weight and high strength; they are widely used in various thermal insulation fields. However, aerogel materials have poor thermal radiation blocking performance, which hinders the application of aerogel composite fiber materials in fields with high requirements for thermal insulation performance, such as hypersonic engines, aircraft compartments, and high-end equipment. Therefore, how to achieve a significant barrier effect of aerogel composite fibers against heat radiation is crucial. Furthermore, it does not reduce the high heat conduction barrier performance of aerogel composite fibers, while having low density, light weight, and long service life, which has become an urgent problem to be solved in this field. Summary of the Invention
[0003] This invention designs a method for preparing a shielding aerogel composite material, comprising the following steps: S1: The bottom surface of the fiber matrix contacts a metal part to obtain a metal-fiber matrix assembly; S2: Add aluminum source to anhydrous ethanol and deionized water and stir. Add silicon source while stirring to obtain aluminum-silicon composite solution. S3: After the aluminum-silicon composite solution is allowed to stand, propylene oxide is added and stirred to obtain an aluminum-silicon composite sol. The metal-fiber matrix component is placed in the aluminum-silicon composite sol and vacuum impregnated. The aluminum-silicon composite sol is then impregnated into the fiber matrix to obtain a metal-gel-reinforced fiber component. S4: The metal-gel reinforced fiber assembly is aged in an alcohol solution and then subjected to supercritical drying to obtain a metal-fiber reinforced aerogel composite material assembly. Metal-fiber reinforced aerogel composite components include fiber reinforced aerogel composites and metal parts in contact with the fiber reinforced aerogel composites; The bottom surface of the fiber-reinforced aerogel composite material contains metal ions; After supercritical drying, the metal parts are separated from the fiber-reinforced aerogel composite material; The fiber-reinforced aerogel composite material was heat-treated to obtain the shielding layer aerogel composite material. The shielding layer aerogel composite material includes a fiber-reinforced aerogel composite material body and a shielding layer connected to the fiber-reinforced aerogel composite material body; the shielding layer includes a metal oxide.
[0004] Compared with the prior art, the beneficial effects of the present invention are as follows: by placing the metal-fiber matrix assembly in the aluminum-silicon composite sol and performing vacuum impregnation, the aluminum-silicon composite sol corrodes the metal parts to generate metal ions, thereby facilitating the uniform entry of metal ions into the aluminum-silicon composite sol impregnated on the bottom surface of the fiber matrix and the metal part matrix. By aging the metal-gel-reinforced fiber assembly in an alcohol solution and then subjecting it to supercritical drying, metal ions can be further introduced into the fiber matrix. This facilitates the formation of a shielding layer of a certain thickness on the surface of the fiber matrix. After heat treatment, the metal ions are oxidized and generate a radiation shielding layer containing metal oxides in situ on the outer surface of the aerogel. This allows the fiber-reinforced aerogel composite material body and the shielding layer to be integrally formed, achieving significant heat radiation barrier performance of the aerogel composite fiber without reducing its high heat conduction barrier performance. It also features low density, light weight, and long service life. By forming a microscopic coating layer containing metal ions on the surface, the problems of uneven doping, complex processes, high costs, and poor interfacial adhesion of traditional radiation-resistant agents are solved, thus improving the radiation shielding effect and application range. It can significantly improve the thermal insulation performance of aerogel composite materials. At the same time, it can avoid the destruction of aluminum-oxygen bond connections in the three-dimensional network skeleton by the doping of other light-shielding agents, and avoid the collapse of the nanostructure of the three-dimensional network skeleton during heating, which would affect the integrity of the three-dimensional network skeleton and facilitate the formation of a three-dimensional network skeleton structure with better thermal insulation effect.
[0005] Furthermore, the fiber matrix in S1 is one or more of the following: aluminosilicate fiber felt, alumina fiber felt, mullite fiber felt, quartz fiber felt, basalt fiber felt, and high silica fiber felt.
[0006] The beneficial effect of adopting the above-mentioned further technical solution is that the fiber matrix can serve as a reinforcement for the aerogel, enabling the prepared aerogel composite material to have better thermal insulation effect.
[0007] Furthermore, the metal component in S1 is one of a metal plate, a metal mesh, and a metal box; The iron content of the metal component is ≥60%; When the metal part is a metal mesh, the mesh count of the metal mesh is 100-300 mesh.
[0008] The beneficial effects of adopting the above-mentioned further technical solutions are as follows: by using metal plates, metal meshes, or metal boxes as metal parts, the outer surface layer of aerogel and fibers can be partially surrounded, and shielding layers of different shapes can be prepared on the outer surface of aerogel, which is conducive to the preparation of aerogel composite materials with different thermal insulation effects; by using metal parts with an iron content of ≥60%, it is beneficial to allow metal ions to penetrate into the interior of aerogel; by using metal mesh with a mesh size of 100-300 mesh, it is beneficial to form a mesh structure on the surface of aerogel, while also achieving good thermal insulation effect.
[0009] Furthermore, the aluminum source, silicon source, anhydrous ethanol, and deionized water are stirred and mixed at room temperature for 0.8-1.2 hours; the molar ratio of the silicon source, aluminum source, anhydrous ethanol, and deionized water is 1:3-8:(16-360):(16-180). The aluminum source includes one or more of aluminum chloride, aluminum nitrate, and aluminum acetate; the silicon source includes one or two of tetraethyl orthosilicate and methyl orthosilicate. The pH value of the aluminum-silicon composite solution is adjusted by adding hydrochloric acid, and the pH value of the aluminum-silicon composite solution is 0-2.5.
[0010] Furthermore, the aluminum-silicon composite solution in S3 is allowed to stand at room temperature for 8-24 hours; The molar ratio of propylene oxide to silicon source in S3 is (8-64):1. The propylene oxide and aluminum-silicon composite solution is stirred at room temperature for 3-7 minutes.
[0011] The beneficial effects of adopting the above-mentioned further technical solutions are as follows: adding deionized water promotes hydrolysis, which is conducive to bridging aluminum-oxygen bonds and silicon-oxygen bonds, thereby facilitating the formation of a three-dimensional network framework structure of aerogel after polycondensation; by controlling the pH value of the aluminum-silicon composite solution to 0-2.5, the corrosion effect of the aerogel pre-solution on metal parts can be controlled, which is beneficial to the corrosion of metal parts by the aluminum-silicon composite solution; the addition of propylene oxide can consume hydrogen ions in the aluminum-silicon composite solution, slowly increase the pH value, delay the polycondensation reaction, promote full hydrolysis, form a stronger gel network, and at the same time improve the corrosion performance of the aluminum-silicon composite sol, enabling better corrosion of metal parts during the aging process.
[0012] Furthermore, the process of obtaining a metal-fiber matrix assembly by contacting the bottom surface of the fiber matrix with the metal component includes: The fiber matrix is placed in a metal box, the bottom of which is a metal plate. The sidewalls are mesh structures, and the fiber matrix is brought into contact with the bottom surface of the metal box to obtain the metal-fiber matrix assembly.
[0013] The beneficial effects of adopting the above-mentioned further technical solution are as follows: the aluminum-silicon composite sol enters the interior of the fiber matrix through the mesh structure of the metal sidewall, so that the fiber matrix comes into contact with the bottom surface of the metal box. The aluminum-silicon composite sol corrodes the metal parts, so that the metal ions of the metal parts continuously penetrate into the fiber matrix, thereby preparing a metal-fiber matrix component. Furthermore, the step of preparing the metal-gel reinforced fiber assembly in S3 is as follows: the aluminum-silicon composite sol is placed into the impregnation container, and the metal-fiber matrix assembly is placed into the impregnation container containing the aluminum-silicon composite sol for vacuum impregnation to obtain the metal-gel reinforced fiber assembly. The vacuum impregnation pressure is -0.05~-0.1MPa. During the impregnation process, the aluminum-silicon composite sol is heated at a temperature of 45-65℃, and the impregnation time is 1-10h.
[0014] The beneficial effects of adopting the above-mentioned further technical solutions are as follows: by vacuum impregnating the fiber matrix in the impregnation container, the impregnation effect of the fiber can be improved; by heating during the impregnation process, the corrosion effect of the metal parts can be further improved, which is conducive to the preparation of aerogel composite materials with significant heat insulation effect.
[0015] Furthermore, the alcohol solution in S4 is anhydrous ethanol or a mixture of anhydrous ethanol and tetraethyl orthosilicate, wherein the volume ratio of tetraethyl orthosilicate to anhydrous ethanol is 1:(5-20), the alcohol solution in the aging process is replaced once every 8-12 hours, the number of replacements is 4-8 times, and the aging temperature is 50-70℃. and / or The supercritical drying temperature in S4 is 250-290℃, and the supercritical pressure is... 7.5-10MPa.
[0016] The beneficial effects of adopting the above-mentioned further technical solutions are as follows: by adding an alcohol solution with a small specific surface area and aging it with a solution of low surface tension, the water inside the aerosol is displaced, allowing the three-dimensional network skeleton structure to continue to grow and improving the strength of the three-dimensional network skeleton. At the same time, aging in a high-temperature and high-humidity environment and controlling the aging time helps to control the corrosion of metal parts by the aerosol, thereby regulating the thickness of the shielding layer and realizing the integration of the shielding layer with the substrate, avoiding the risk of detachment at high temperatures. By using supercritical drying, it is beneficial to maintain the nanopores of the three-dimensional network structure of the aerosol and avoid the phenomenon of nanopore collapse when polymers volatilize, further improving the thermal insulation effect of the aerogel.
[0017] Furthermore, in S4, the heat treatment temperature is 500-700℃, the heat treatment atmosphere is air, the heat treatment time is 0.8h-6.5h, and the heat treatment heating rate is 1~10℃ / min.
[0018] The beneficial effects of adopting the above-mentioned further technical solution are as follows: through heat treatment, the aerogel fiber preform is cured, and at the same time, the metal ions inside the cured aerogel fiber preform are oxidized in situ, thereby forming a radiation shielding layer on the outer surface of the aerogel fiber preform. The radiation shielding layer has a shielding effect on infrared radiation at high temperature, which can significantly improve the thermal insulation performance of aerogel composite materials.
[0019] Furthermore, it also includes surface modification of the fiber-reinforced aerogel composite material in step S4; The surface modifier is one of hexamethyldisilazane, trimethylchlorosilane, methyltrimethoxysilane, dimethyldimethoxysilane, or trimethylmethoxysilane; The mass ratio of the modifier to the fiber-reinforced aerogel composite material is 1:(8-15), the surface modification temperature is 50-120℃, and the surface modification time is 12-48h.
[0020] The beneficial effects of adopting the above-mentioned further technical solutions are as follows: by adding a modifier, the hydroxyl groups inside the fiber-reinforced aerogel composite material can be replaced, which is beneficial for moisture resistance and good heat insulation. Attached Figure Description
[0021] Figure 1 The figure shows the static thermal test results of the aerogel composite material of Example 1 under the following conditions: heating time of 100s, light-facing surface temperature of 1000℃, and heat preservation time of 1000s under quartz lamp conditions. Figure 2 The figure shows the static thermal test results of the aerogel composite material in Example 2 under the following conditions: heating time of 100s, light-facing surface temperature of 1000℃, and heat preservation time of 1000s under quartz lamp conditions. Detailed Implementation To make the objectives, technical solutions, and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.
[0022] Example 1: This embodiment provides a method for preparing a shielding aerogel composite material, including the following steps: S1: The bottom surface of the fiber matrix is in contact with a metal part to obtain a metal-fiber matrix assembly; S2: An aluminum source is added to anhydrous ethanol and deionized water and stirred, while a silicon source is added during stirring to obtain an aluminum-silicon composite solution; S3: After the aluminum-silicon composite solution is allowed to stand, propylene oxide is added and stirred to obtain an aluminum-silicon composite sol. The metal-fiber matrix assembly is placed in the aluminum-silicon composite sol and vacuum impregnated to immerse the aluminum-silicon composite sol into the fiber matrix, resulting in a metal-gel reinforced fiber assembly; S4: The metal-gel reinforced fiber assembly is aged in an alcohol solution. Supercritical drying yields a metal-fiber reinforced aerogel composite component; the metal-fiber reinforced aerogel composite component includes a fiber reinforced aerogel composite material and a metal part in contact with the fiber reinforced aerogel composite material; the surface layer of the bottom surface of the fiber reinforced aerogel composite material contains metal ions; after supercritical drying, the metal part is separated from the fiber reinforced aerogel composite material; the fiber reinforced aerogel composite material is heat-treated to obtain a shielding layer aerogel composite material; the shielding layer aerogel composite material includes a fiber reinforced aerogel composite material body and a shielding layer connected to the fiber reinforced aerogel composite material body; the shielding layer includes metal oxides. The metal-fiber matrix assembly is placed in an aluminum-silicon composite sol for vacuum impregnation. The aluminum-silicon composite sol corrodes the metal parts, generating metal ions, which facilitates the uniform entry of metal ions into the aluminum-silicon composite sol impregnated on the bottom surface of both the fiber matrix and the metal part matrix. The metal-gel-reinforced fiber assembly is then aged in an alcohol solution followed by supercritical drying, which further facilitates the entry of metal ions into the fiber matrix and helps control the formation of a shielding layer of a certain thickness on the fiber matrix surface. After heat treatment, the metal ions are oxidized and in situ, generating a radiation shielding layer containing metal oxides on the outer surface of the aerogel. This integrates the fiber-reinforced aerogel composite material and the shielding layer into a single unit, achieving aerogel composite... Aerogel composite fibers exhibit significant heat radiation blocking properties without compromising their high heat conduction blocking performance. They also boast low density, light weight, and long service life. The formation of a microscopic metal ion-containing coating layer on the surface solves problems such as uneven doping of traditional radiation-resistant agents, complex processes, high costs, and poor interfacial adhesion of surface coatings. This improves the radiation shielding effect and application range, significantly enhancing the thermal insulation performance of aerogel composite materials. Furthermore, it avoids the disruption of aluminum-oxygen bond connections in the three-dimensional network skeleton caused by other light-shielding agents, preventing the collapse of the nanostructure during heating and ensuring the integrity of the three-dimensional network skeleton. This facilitates the formation of a three-dimensional network skeleton structure with better thermal insulation.
[0023] The fiber matrix in S1 is aluminum silicate fiber felt. The fiber matrix can serve as a reinforcement for the aerogel, giving the prepared aerogel composite material better thermal insulation properties.
[0024] In S1, the metal component is a metal plate; the iron content of the metal component is 80%. Using a metal plate as the metal component, the metal plate is pressed onto the outside of the fiber matrix, and then the fiber matrix with the metal plate is placed in the gel pre-forming liquid, allowing the gel pre-forming liquid to penetrate the fiber felt. The metal plate can partially surround the outer surface of the aerogel and fiber, which is beneficial for preparing aerogel composite materials with different thermal insulation effects.
[0025] The aluminum source, silicon source, anhydrous ethanol, and deionized water were stirred and mixed at room temperature for 1 hour; the molar ratio of the silicon source, aluminum source, anhydrous ethanol, and deionized water was 1:5:180:110. The aluminum source includes aluminum acetate; the silicon source includes tetraethyl orthosilicate; The pH value of the aluminum-silicon composite solution is adjusted by adding hydrochloric acid, and the pH value of the aluminum-silicon composite solution is 1.2.
[0026] The aluminum-silicon composite solution in S3 is allowed to stand at room temperature for 15 hours. The molar ratio of propylene oxide to silicon source in S3 is 35:1. The propylene oxide and aluminum-silicon composite solution are stirred at room temperature for 5 minutes. Adding deionized water promotes hydrolysis. During hydrolysis, the hydroxyl groups in anhydrous ethanol are opened, which facilitates the bridging of aluminum-oxygen and silicon-oxygen bonds, thus promoting the formation of a three-dimensional network framework structure of the aerogel after polycondensation. The pH of the aluminum-silicon composite solution is controlled at 1.2, thus controlling the corrosion effect of the aerogel pre-solvent on the metal parts. Alternatively, the pH of the aluminum-silicon composite solution can be controlled at 0-2.5, further facilitating corrosion. The addition of propylene oxide consumes hydrogen ions in the aluminum-silicon composite solution, slowly increasing the pH, delaying the polycondensation reaction, promoting complete hydrolysis, forming a stronger gel network, and improving the corrosion performance of the aluminum-silicon composite sol, enabling better corrosion of metal parts during aging.
[0027] The process of obtaining a metal-fiber matrix assembly by contacting the bottom surface of a fiber matrix with a metal component includes: placing the fiber matrix into a metal box, wherein the bottom surface of the metal box is a metal plate and the metal sidewalls are a mesh structure; and contacting the fiber matrix with the bottom surface of the metal box to obtain the metal-fiber matrix assembly. An aluminum-silicon composite sol enters the fiber matrix through the mesh structure of the metal sidewalls, bringing the fiber matrix into contact with the bottom surface of the metal box. The aluminum-silicon composite sol corrodes the metal component, allowing metal ions from the metal component to continuously penetrate into the fiber matrix, thereby preparing the metal-fiber matrix assembly. The steps for preparing the metal-gel reinforced fiber assembly in S3 are as follows: placing the aluminum-silicon composite sol into an impregnation container, and then placing the metal-fiber matrix assembly into the impregnation container containing the aluminum-silicon composite sol for vacuum impregnation to obtain the metal-gel reinforced fiber assembly. The vacuum impregnation pressure is 0.05, and the aluminum-silicon composite sol is heated during the impregnation process to a temperature of 55°C for 5 hours. The fiber matrix with the metal parts attached is then removed after impregnation, yielding the impregnated fiber matrix. Vacuum impregnation of the fiber matrix within the impregnation container improves the impregnation effect, and heating during the impregnation process further enhances the corrosion resistance of the metal parts, thus facilitating the preparation of aerogel composite materials with significant thermal insulation properties.
[0028] The alcohol solution in S4 is anhydrous ethanol or a mixture of anhydrous ethanol and tetraethyl orthosilicate, with a volume ratio of tetraethyl orthosilicate to anhydrous ethanol of 1:12. The alcohol solution is replaced every 10 hours during the aging process, for a total of 6 replacements. The aging temperature is 55°C. By adding an alcohol solution with a small specific surface area and using a solution with low surface tension for aging, water inside the aerosol is displaced, allowing the 3D network skeleton structure to continue growing and improving its strength. Aging is also performed in a high-temperature and high-humidity environment. By controlling the aging time, it is beneficial to control aerosol corrosion of metal parts, thereby regulating the thickness of the shielding layer and achieving integration between the shielding layer and the substrate, avoiding the risk of detachment at high temperatures.
[0029] The supercritical drying temperature in S4 is 260℃, and the supercritical pressure is 8.5MPa. Using supercritical drying helps maintain the three-dimensional network structure of the aerosol's nanopores, preventing the collapse of the nanopores when polymers volatilize, and further improving the thermal insulation effect of the aerogel.
[0030] The heat treatment temperature in step S4 is 600℃, the heat treatment atmosphere is air, the heat treatment time is 3.2 hours, and the heating rate is 5℃ / min. Through heat treatment, the aerogel fiber preform is solidified, and simultaneously, the metal ions inside the solidified aerogel fiber preform are oxidized in situ, thereby forming a radiation shielding layer on the outer surface of the aerogel fiber preform. This radiation shielding layer has a shielding effect on infrared radiation at high temperatures, significantly improving the thermal insulation performance of the aerogel composite material.
[0031] The process also includes surface modification of the fiber-reinforced aerogel composite material in step S4; the surface modifier is trimethylchlorosilane; the mass ratio of the modifier to the fiber-reinforced aerogel composite material is 1:12; the surface modification temperature is 80℃; and the surface modification time is 25 hours. Adding the modifier can replace the hydroxyl groups inside the fiber-reinforced aerogel composite material, which is beneficial for moisture resistance and good heat insulation.
[0032] The influence of static thermal testing of a quartz lamp on the thermal insulation performance of a radiation shielding layer material was compared. Tests were conducted under the following conditions: sample thickness 10 mm, heating time 100 s, light-facing surface temperature 1000℃, and holding time 1000 s. The test results are as follows: Figure 1 As shown: the diffusion depth of the radiation shielding layer is about 1 mm, and the actual temperature of the sample's back surface is basically stable at 300~310℃; Example 2: The content that is the same as in Example 1 will not be repeated here; the differences between this embodiment and Example 1 are as follows: The fiber matrix in S1 is aluminum silicate fiber felt and alumina fiber felt. The process of obtaining a metal-fiber matrix assembly by contacting the bottom surface of the fiber matrix with the metal part includes: placing the fiber matrix in a metal box, the bottom surface of the metal box being a metal plate and the metal sidewall being a mesh structure; contacting the fiber matrix with the bottom surface of the metal box to obtain the metal-fiber matrix assembly; the aluminum-silicon composite sol entering the interior of the fiber matrix through the mesh structure of the metal sidewall, making the fiber matrix contact the bottom surface of the metal box; the aluminum-silicon composite sol corroding the metal part, allowing metal ions from the metal part to continuously penetrate into the fiber matrix, thereby preparing the metal-fiber matrix assembly. The iron content of the metal part in S1 is 98%.
[0033] The aluminum source, silicon source, anhydrous ethanol, and deionized water were stirred and mixed at room temperature for 1.1 hours; the molar ratio of the silicon source, aluminum source, anhydrous ethanol, and deionized water was 1:7:350:175. The aluminum source includes aluminum acetate; the silicon source includes tetraethyl orthosilicate; the pH value of the aluminum-silicon composite solution is adjusted by adding hydrochloric acid, and the pH value of the aluminum-silicon composite solution is 2.4; the aluminum-silicon composite solution in S3 is allowed to stand at room temperature for 23 hours. The molar ratio of propylene oxide to the silicon source in S3 is 62:1, and the propylene oxide and aluminum-silicon composite solution are stirred at room temperature for 6 minutes. The vacuum impregnation pressure is 0.09, and the aluminum-silicon composite sol is heated during the impregnation process at a temperature of 63°C for 9 hours.
[0034] The alcohol solution in S4 is a mixture of anhydrous ethanol and tetraethyl orthosilicate, with a volume ratio of tetraethyl orthosilicate to anhydrous ethanol of 1:18. The alcohol solution in the aging process is replaced every 11 hours for a total of 7 times, and the aging temperature is 68°C.
[0035] The supercritical drying temperature in S4 is 280°C, and the supercritical pressure is 9.5 MPa.
[0036] The heat treatment temperature in S4 is 680℃, the heat treatment atmosphere is air, the heat treatment time is 6.4h, and the heat treatment heating rate is 9℃ / min.
[0037] The modifier in S4 is dimethyldimethoxysilane; the mass ratio of the modifier to the fiber-reinforced aerogel composite material is 1:14; the surface modification temperature is 115℃; and the surface modification time is 45 hours. Adding the modifier can replace the hydroxyl groups inside the fiber-reinforced aerogel composite material, which is beneficial for moisture resistance and good heat insulation.
[0038] Test results are as follows Figure 2 As shown: Without a radiation shielding layer, the actual temperature of the sample's back surface remained basically stable between 335 and 350℃.
[0039] Example 3: The content that is the same as in Example 2 will not be repeated here; the differences between this embodiment and Example 2 are as follows: The fiber felt in S1 is a mullite fiber felt and a quartz fiber felt; the metal part is a metal mesh. The metal mesh is pressed onto the outside of the fiber matrix, and then the fiber matrix with the metal mesh is placed in the gel pre-preparation liquid, so that the gel pre-preparation liquid is immersed in the fiber felt.
[0040] The metal component in S1 has an iron content of 65%, and the metal mesh has a mesh size of 200. The 65% iron content of the metal component facilitates the penetration of the metal into the interior of the aerogel, while the 200-mesh metal mesh facilitates the formation of a mesh structure on the surface of the aerogel, resulting in good thermal insulation.
[0041] The aluminum source, silicon source, anhydrous ethanol, and deionized water were mixed and stirred at room temperature for 0.9 h. The molar ratio of the silicon source, aluminum source, anhydrous ethanol, and deionized water was 1:4:18:18. The aluminum source included aluminum nitrate, and the silicon source included methyl orthosilicate. The pH of the aluminum-silicon composite solution was adjusted by adding hydrochloric acid, and the pH of the aluminum-silicon composite solution was 0.5. The aluminum-silicon composite solution in step S3 was allowed to stand at room temperature for 9 h. In step S3, the molar ratio of propylene oxide to silicon source was 9:1, and the propylene oxide and aluminum-silicon composite solution were stirred at room temperature for 4 min.
[0042] The vacuum impregnation pressure is -0.01 MPa, and the aluminum-silicon composite sol is heated during the impregnation process at a temperature of 47°C for 2 hours.
[0043] The alcohol solution in S4 is anhydrous ethanol, the volume ratio of tetraethyl orthosilicate to anhydrous ethanol is 1:7, the alcohol solution in the aging process is replaced once every 9 hours, the number of replacements is 5, and the aging temperature is 62℃.
[0044] The supercritical drying temperature in S4 is 260°C, and the supercritical pressure is 7.8 MPa.
[0045] The heat treatment temperature in S4 is 520℃, the heat treatment time is 0.9h, and the heating rate of the heat treatment is 2℃ / min.
[0046] The modifier in S4 is trimethylchlorosilane; the mass ratio of the modifier to the shielding layer aerogel preform is 1:9; the surface modification temperature is 60℃; and the surface modification time is 13h.
[0047] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a shielding aerogel composite material, characterized in that: Includes the following steps: S1: The bottom surface of the fiber matrix comes into contact with the metal part to obtain a metal-fiber matrix assembly; S2: Add aluminum source to anhydrous ethanol and deionized water and stir. Add silicon source while stirring to obtain aluminum-silicon composite solution. S3: After the aluminum-silicon composite solution is allowed to stand, propylene oxide is added and stirred to obtain an aluminum-silicon composite sol. The metal-fiber matrix component is placed in the aluminum-silicon composite sol and vacuum impregnated. The aluminum-silicon composite sol is then impregnated into the fiber matrix to obtain a metal-gel-reinforced fiber component. S4: The metal-gel reinforced fiber assembly is aged in an alcohol solution and then subjected to supercritical drying to obtain a metal-fiber reinforced aerogel composite material assembly. Metal-fiber reinforced aerogel composite components include fiber reinforced aerogel composites and metal parts in contact with the fiber reinforced aerogel composites; The bottom surface of the fiber-reinforced aerogel composite material contains metal ions; Separate the metal parts from the fiber-reinforced aerogel composite material; The fiber-reinforced aerogel composite material was heat-treated to obtain the shielding layer aerogel composite material. The shielding layer aerogel composite material includes a fiber-reinforced aerogel composite material body and a shielding layer connected to the fiber-reinforced aerogel composite material body; the shielding layer includes a metal oxide.
2. The method for preparing a shielding aerogel composite material according to claim 1, characterized in that: The fiber matrix in S1 is one or more of the following: aluminosilicate fiber felt, alumina fiber felt, mullite fiber felt, quartz fiber felt, basalt fiber felt, and high silica fiber felt.
3. The method for preparing a shielding aerogel composite material according to claim 1, characterized in that: The metal component in S1 is one of a metal plate, a metal mesh, and a metal box; The iron content of the metal component is ≥60%; When the metal part is a metal mesh, the mesh count of the metal mesh is 100-300 mesh.
4. The method for preparing a shielding aerogel composite material according to claim 1, characterized in that: The aluminum source, silicon source, anhydrous ethanol, and deionized water were stirred and mixed at room temperature for 0.8-1.2 hours. The molar ratio of the silicon source, aluminum source, anhydrous ethanol and deionized water is 1:3-8:(16-360):(16-180). The aluminum source includes one or more of aluminum chloride, aluminum nitrate, and aluminum acetate; the silicon source includes one or two of tetraethyl orthosilicate and methyl orthosilicate. The pH value of the aluminum-silicon composite solution is adjusted by adding hydrochloric acid, and the pH value of the aluminum-silicon composite solution is 0-2.
5.
5. The method for preparing a shielding aerogel composite material according to claim 1, characterized in that: The aluminum-silicon composite solution in S3 is left to stand at room temperature for 8-24 hours. The molar ratio of propylene oxide to silicon source in S3 is (8-64):
1. The propylene oxide and aluminum-silicon composite solution is stirred at room temperature for 3-7 minutes.
6. The method for preparing a shielding aerogel composite material according to claim 3, characterized in that: The process of obtaining a metal-fiber matrix assembly by contacting the bottom surface of the fiber matrix with the metal component includes: The fiber matrix is placed in a metal box, the bottom of which is a metal plate. The sidewalls are mesh structures, and the fiber matrix is brought into contact with the bottom surface of the metal box to obtain the metal-fiber matrix assembly.
7. The method for preparing a shielding aerogel composite material according to claim 1, characterized in that: The steps for preparing the metal-gel reinforced fiber assembly in S3 are as follows: placing the aluminum-silicon composite sol into an impregnation container, and then placing the metal-fiber matrix assembly into the impregnation container containing the aluminum-silicon composite sol for vacuum impregnation to obtain the metal-gel reinforced fiber assembly. The vacuum impregnation pressure is -0.05~-0.1MPa. During the impregnation process, the aluminum-silicon composite sol is heated at a temperature of 45-65℃, and the impregnation time is 1-10h.
8. The method for preparing a shielding aerogel composite material according to claim 1, characterized in that: The alcohol solution in S4 is anhydrous ethanol or a mixture of anhydrous ethanol and tetraethyl orthosilicate, wherein the volume ratio of tetraethyl orthosilicate to anhydrous ethanol is 1:(5-20). The alcohol solution in the aging process is replaced once every 8-12 hours, and the number of replacements is 4-8 times. The aging temperature is 50~70℃. and / or The supercritical drying temperature in S4 is 250-290℃, and the supercritical pressure is... 7.5-10MPa.
9. The method for preparing a shielding aerogel composite material according to claim 1, characterized in that: The heat treatment temperature in S4 is 500-700℃, the heat treatment atmosphere is air, the heat treatment time is 0.8h-6.5h, and the heat treatment heating rate is 1~10℃ / min.
10. The method for preparing a shielding aerogel composite material according to claim 1, characterized in that: It also includes surface modification of the fiber-reinforced aerogel composite material in step S4; The surface modifier is one of hexamethyldisilazane, trimethylchlorosilane, methyltrimethoxysilane, dimethyldimethoxysilane, or trimethylmethoxysilane; The mass ratio of the modifier to the fiber-reinforced aerogel composite material is 1:(8-15), the surface modification temperature is 50-120℃, and the surface modification time is 12-48h.